ANALISIS PEMAHAMAN KONSEP ALJABAR MAHASISWA CALON GURU MELALUI PETA KONSEP PADA PROGRAM STUDI PENDIDIKAN MATEMATIKA UNIVERSITAS ABULYATAMA ACEH - Ade Irfan; Anzora Anzora (Jurnal Dedikasi Pendidikan, 2017)
Understanding is the ultimate goal to be achieved from each strategy applied learning in the learning process. However, teachers generally do not know the specific tool that can measure the understanding and misconceptions. Novak refers to the theories Ausubel said that these problems can be solved with a concept map. According to Novak, Concept Map can be applied with the purpose of (1) investigate what is already known by students, (2) learn how to learn, (3) reveal misconceptions, and (4) an evaluation tool. Algebra is one of the materials that are important in mathematics. The mistake in understanding the concept of algebra will impact on the erroneous understanding of other materials, because algebra is one of the foundations of mathematics. Therefore, understanding the concepts and misconceptions that occur in algebra important to know. This study aimed to describe understanding of algebra concepts, find misconceptions as well as evaluating the lecturing process that has been going on mathematics education of Abulyatama University. To achieve these objectives, the researchers used a method-descriptive exploratory study with a qualitative approach. Subjects were pre-service teacher in mathematics education, The Faculty of Education, Abulyatama University. Researchers became the main instrument, while supporting instruments namely; concept mapping assignment sheet (LTPK), the questionnaire, questionnaire responses and the recorder. Data validity checking carried out by the same method on different sources, called triangulation method. Data analysis was performed with the stage offered by Miles and Huberman, namely; (1) data reduction, (2) presentation of data, and (3) conclusion. The results showed that the understanding of algebra concept of pre-service teacher using a concept map on Mathematics Education is at the level of misconceptions portion (MSG). The misconception algebra of pre-service teacher in mathematics education using concept maps happen to identify a secondary idea, in determining the type of map concepts and reasons for selecting it, and in clarifying the relationship with the main idea of secondary ideas. The response of pre-service teacher to the lecture algebra is positive (3.27).